Developing Learners' Digital Literacy through Guided Discovery Learning on the Matter of Work and Energy - Rahman, Faisal; Suyidno, Suyidno; Miriam, Sarah; Husain, Sadang (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Digital literacy is essential in educational field and digital society, but it has received less attention in schools. Objective:  This paper will analyze the effectiveness of work and energy teaching materials through guided discovery learning to improve students' digital literacy.  Method: This study applied a one-group pretest and posttest design on 26 secondary level students of grade X. Data collection techniques used digital literacy questionnaire instruments, learning outcomes tests, and interviews. Results: The results showed that the n-gain of students’ digital literacy and learning outcomes were medium criteria and high criteria, respectively. Thus, the developed physics teaching materials through guided discovery learning are effective for improving students' digital literacy. Novelty: Previous studies have not used guided discovery on work and energy teaching material to train students' digital literacy.